Histological Study of Mudskipper (Periophthalmus gracilis) Gills - Supriyati, Hikmah; Apriliani, Nurul Safitri; Luthfi, Muhammad Ja’far (Proceeding International Conference on Science and Engineering, 2019)
Mudskipper belongs to the Gobiidae family which has respiratory adaptation to fits their habitat. Mudskipper has a different gill structure or modification of gills, this different structure allows the mudskipper to survive for a long time outside water. This study aimed to determine the histology of gills and find out whether there is a modification of gills in the mudskipper respiratory organs (Periophthalmus gracilis). Histological preparations were done using paraffin method, stained with Hematoxylin-Eosin. Data analysis was carried out in a qualitative descriptive. The results showed that there is no additional respiratory organ in the mudskipper respiration, whereas the gills have some modifications. The histological structure of mudskipper gills consists of gill arches, arteries, gill filament, primary lamellae, and secondary lamellae. The gills of mudskipper have a different structure from the general fish, which has a thick secondary lamellae with a low amount of density, the shape of the filament are short and bent. This gill structure is a form of adaptation to habitat and behavior to live outside the water in a relatively long time.